Copper Catalysts for Selective CC Bond Cleavage of β‐O‐4 Lignin Model Compounds. Issue 17 (26th September 2014) - Sedai, Baburam; Baker, R. Tom
Abstract The reactivity of homogeneous copper catalysts towards the selective CC bond cleavage of both phenolic and non‐phenolic arylglycerol β‐aryl ether lignin model compounds has been explored. Several copper precursors, nitrogen ligands, and solvents were evaluated in order to optimize the catalyst system. Using the optimized catalyst system, copper(I) trifluoromethanesulfonate [Cu(OTf)]/L/TEMPO (L=2, 6‐lutidine, TEMPO=2, 2, 6, 6‐tetramethyl‐piperidin‐1‐yl‐oxyl), aerobic oxidation of the non‐phenolic β‐O‐4 lignin model compound proceeded with good selectivity for CαCβ bond cleavage, affording 3, 5‐dimethoxybenzaldehyde as the major product. Aerobic oxidation of the corresponding phenolic β‐O‐4 lignin model proceeded with different selectivity, affording 2, 6‐dimethoxybenzoquinone and α, β‐unsaturated aldehyde products resulting from cleavage of the CαCaryl bond. At low catalyst concentrations, however, a change in selectivity was observed as oxidation of the benzylic secondary alcohol predominated with both substrates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>